2020
DOI: 10.1002/micr.30660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arterial supercharging and venous superdrainage on improvement of survival of the extended perforator flap in rats

Abstract: Background Arterial supercharging and venous superdrainage have been the commonly used vascular augmentation techniques for resolving partial loss of flaps in reconstructive surgery. It remains controversial which one of them is more effective in improving flap survival. The purpose of this study was to compare the effect of distal venous superdrainage and arterial supercharging on the survival of an extended dorsal perforator flap in rats. Materials and Methods Sixty Sprague–Dawley rats were randomly divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Inner flap anastomosis (also called intraflap anastomosis, or turbocharging) is a powerful technique to reconstruct huge free flaps without necrosis. [23][24][25][26][27][28] However, definition of "a large flap" is not established, and a subjective perspective is involved for determination. Through this study, we tried to investigate the circulation area that a single perforator supplies to anterolateral thigh flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Inner flap anastomosis (also called intraflap anastomosis, or turbocharging) is a powerful technique to reconstruct huge free flaps without necrosis. [23][24][25][26][27][28] However, definition of "a large flap" is not established, and a subjective perspective is involved for determination. Through this study, we tried to investigate the circulation area that a single perforator supplies to anterolateral thigh flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this is a good method for treating moderate-scale scars in Zone LC. Some studies have confirmed that only arterial or venous anastomosis can also achieve good effects to the distal end of the flap, which warrants further study 20,21 …”
Section: Discussionmentioning
confidence: 95%
“…Some studies have confirmed that only arterial or venous anastomosis can also achieve good effects to the distal end of the flap, which warrants further study. 20,21 Unilateral Pedicled Plus Contralateral Super Thin Forehead Flaps When the contralateral vessels are injured or microsurgery cannot be performed for technical reasons, another choice should be applied. We successfully used the super thin flap to solve this problem.…”
Section: Unilateral Pedicled Plus Contralateral Vascular Anastomosis ...mentioning
confidence: 99%
“…A number of studies encourage reduction of flap necrosis by arterial supercharge. Wang et al 53 found that the extent of dilation of 19 Furthermore, previous studies have shown that the distal arterial supercharging that leads to marked dilation of the choke vessels among the territories is more effective than proximal arterial supercharging. 21 Arterialized venous supercharged (AVS) flap is a "hybrid perfusion" mode by anastomosing a distal vein of the flap with a recipient artery, which is different from the established one of arterial supercharging or venous superdrainage.…”
Section: Arterial Superchargementioning
confidence: 99%